1987
DOI: 10.1111/j.1532-5415.1987.tb01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Depression and Burden for Informal Caregivers of Patients in a Geriatrics Referral Clinic

Abstract: Caregiver burden has been associated with patient dementia. In this study we tested the hypothesis that caregiver burden and depression are related to patient cognitive impairment. We analyzed records of 127 elderly male patients from a Veterans hospital geriatrics referral clinic. The patients and their informal caregivers had been referred to the clinic because the complexity and multiplicity of their problems were beyond the treatment capability of other clinics. There was a high prevalence of dementia (73%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
3
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 15 publications
5
58
3
1
Order By: Relevance
“…A substantial number of the spouses reported that they were depressed by the situation, that their social life was affected, and that it was difficult to get away on holiday. Similar problems have been reported in previous studies (6,18).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A substantial number of the spouses reported that they were depressed by the situation, that their social life was affected, and that it was difficult to get away on holiday. Similar problems have been reported in previous studies (6,18).…”
Section: Discussionsupporting
confidence: 60%
“…However, there is good reason to believe that the mean age of the spouses was similar to that of the patients considering the similar number of males and females in the sample. A substantial number of studies have documented the strain resulting from caring for a relative suffering from dementia, and also the association between depression suffered by the carer and depressive symptoms of the patient (1,2,18). However, to our knowledge, all previous reports have included patients more severely demented than those in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Various studies reported that 40%-83% of caregivers for dementia patients met the criteria for depressive disorders [8][9][10]. However, few studies on the prevalence of depression in caregivers for the disabled Reprint requests to: Yoshie Yokoyama, Department of Public Health, Kinki University School of Medicine, 377, Ohnohigashi, Osakasayama city, Osaka 589, Japan elderly have been done using population data in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In six of these studies (111)(112)(113)119,128,133), caregivers were compared with noncaregivers whereas, in six studies (117,118,122,127,139,142), caregivers for demented patients were compared with caregivers of patients with other impairments. In the absence of a comparison group, it is impossible to quantify the impact of caregiving, since "background" levels of morbidity cannot be controlled for.…”
Section: A Identification Of Studiesmentioning
confidence: 99%